Naval Narratives of Re-enactment: In Which We Serve and Sea of Fire. (2nd October 2017) - Rayner, Jonathan
Abstract : This essay examines two narrative examples of the Royal Navy and naval combat on screen, exploring their resemblances in the re-enactment of naval history and their portrayal of the past through consistent representational strategies. In Which We Serve (Noel Coward and David Lean, 1942) and Sea of Fire (Ian Duncan, 2007) use deliberate and self-conscious recreations of the past to authenticate their interpretations of British naval history, and evince comparably conservative stances towards the Royal Navy and perceptions of its traditions. The similarity of their narratives, which describe the events leading up to the loss of two Navy destroyers, helps to reveal and reinforce the tonal, structural, and stylistic parallels in their depictions. The correspondence in their portrayal of naval combat and the institution of the Royal Navy illustrates the consistencies of representation which characterize the naval war film as a distinctive, definable narrative form. Above all, their commitment to the recreation and re-enactment of identifiable historical events underpins their importance in the representation and commemoration of the national, naval past. It is this aspect of both productions which is significant in the exploration of the role of visual representations to construct, affirm, and broadcast pervasive and persuasive versions of popular history.